EFEKTIVITAS PELAKSANAAN PROGRAM KELUARGA BERENCANA - ', Merrynce; Hidir, Ahmad (Universitas Riau, 2013)
The purpose of thisstudy is to investigate and analyze the factors that influence the effectiveness of the implementationof family planning programs in the Middle District of Kuantan Kuantan District Singingi. Thisresearch was conducted in the Central District of Kuantan Kuantan District Singingi, where theinformant research is that BPMPKB implementers and beneficiaries of the program is public. Datacollected by interview and observation techniques, after the data was collected and then analyzedusing qualitative descriptive analysis. The results show the effectiveness of the implementation offamily planning programs in the Middle District of Kuantan Kuantan District Singingi is quiteeffective. While the dominant factor affecting the effectiveness of the implementation of familyplanning programs is the factor of communication and resource factors.